GAMBARAN KONSEP DIRI PASIEN DENGAN HIV/AIDS - Rozani, Leni; Nurhayati, Nurhayati (JURNAL KEPERAWATAN MUHAMMADIYAH BENGKULU, 2021)
HIV/AIDS is still a major health problem in Indonesia and its incidence rate is the third highest in Asia. People living with HIV/AIDS (PLWHA) often get a negative stigma which has an impact on negative self-concept. This study aims to examine the self-concept of PLWHA. This research was a descriptive study with a cross-sectional design. 40 respondents enrolled in this study, especially PLWHA who underwent routine control in the PKT-VCT Room at the Dr. M. Yunus Hospital in Bengkulu. The self-concept questionnaire was used in this study. The results of this research showed that the majority of respondents experience poor or negative self-concept, especially for female respondents in the age range from 26 to 45 years. These results could be a special concern for health care workers and families to provide full support for PLWHA in improving positive self-concept.Keywords: self-concept, PLWHA, HIV/AIDS